Synthesis of new N, N′-bis[1-aryl-3-(piperidine-1-yl)propylidene]hydrazine dihydrochlorides and evaluation of their cytotoxicity against human hepatoma and breast cancer cells. (June 2014) - Kucukoglu, Kaan; Gul, H. Inci; Cetin-Atalay, Rengul; Baratli, Yosra; Charles, Anne-Laure; Sukuroglu, Murat; Gul, Mustafa; Geny, Bernard
Abstract N, N′-Bis[1-aryl-3-(piperidine-1-yl)propylidene]hydrazine dihydrochlorides were synthesized by the reaction of 2 mols of 1-aryl-3-(piperidine-1-yl)-1-propanone hydrochlorides with 1 mol of hydrazine hydrate. Aryl part was C6H5 (P1), 4-CH3C6H4 (P2), 4-CH3OC6H4 (P3), 4-HOC6H4 (P4), 4-ClC6H4 (P5), 3-CH3OC6H4 (P6), 4-FC6H4 (P7) and 4-BrC6H4 (P8). Except P1, all compounds were reported for the first time. The chemical structures were confirmed by UV, 1H NMR, 13C NMR and HRMS spectra. P1, P2, P7 and P8 against human hepatoma (Huh7) cells and P1, P2, P4, P5, P6, P7 and P8 against breast cancer (T47D) cells have shown cytotoxicity. P1, P2 and P7 had more potent cytotoxicity against Huh7 cells than the reference compound 5-FU, whereas only P2 was more potent than the 5-FU against T47D cells. Representative compound P7 inhibited the mitochondrial respiration at 144, 264 and 424 µM concentrations dose-dependantly in liver homogenates. The results suggest that P1, P2, P7 and P8 may serve as model compounds for further synthetic studies.